DEGRADASI FUNGSI LEGISLASI DPRD DALAM SENTRALISASI KEBIJAKAN PENETAPAN RENCANA TATA RUANG WILAYAH DI KABUPATEN/KOTA - Fanda I'aannah; Agus Tri Widodo (Jendela Inovasi Daerah, 2021)
The issuance of Law Number 11 of 2020 concerning Job Creation has broad implications in various fields/fields, one of which is in the field of determining Regional Spatial Plans in Regencies/Cities. The a quo Law centralizes the policy on the Determination of Regional Spatial Plans in Regencies/Cities. This article addresses three main issues. First, how is the authority of the Regional Government in making arrangements related to the Regency/City Regional Spatial Planning. Second, why centralization is carried out in the determination of Regency/City Regional Spatial Plans. Third, how is the existence of DPRD in implementing the legislative function in determining the Regency/City Spatial Planning. The provisions contained in Law Number 11 of 2020 have an impact on the legislative function of the DPRD which is experiencing degradation. This article uses a normative research method with a conceptual approach and a statutory approach. With the existence of this work copyright law, the regulatory authority has become centralized, although the regions are still given several roles and authorities.